Frank Wood's business accounting 1 - Wood, Frank, Omuya, J.O.; Omuya, J.O (England : Longman, 1982)
this textbook has been written so that a very thorough introduction to accounting is covered in two volumes. the fact that this task has been split between two volumes is a recognition of the fact that, for many students, their grounding in the subject will not have to be as exhaustive as those who will carry on with professional examinations.
Includes index.
jbi, 12/03/2018
Loans
Keywords: Accounting